Influence of Character Development Techniques on Reader Engagement in Kenya - Mbira, Charles (American Journal of Literature Studies, 2024)
Purpose: The aim of the study was to assess the influence of character development techniques on reader engagement in Kenya. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Well-developed characters tend to evoke stronger emotional responses from readers, fostering a deeper connection to the narrative. This emotional resonance can lead to increased empathy and investment in the characters' journeys. Secondly, techniques such as character arcs, internal conflicts, and growth over the course of the story contribute to a sense of realism and complexity, enhancing reader immersion. Additionally, relatable and multi-dimensional characters are more likely to captivate readers, as they can see aspects of themselves reflected in the characters' struggles and triumphs. Furthermore, the effectiveness of character development techniques varies depending on genre and target audience, highlighting the importance of tailoring strategies to fit the specific demands of the narrative. Overall, skillful implementation of character development techniques plays a crucial role in engaging readers and enhancing their overall reading experience. Implications to Theory, Practice and Policy: Social cognitive theory, schema theory and narrative transportation theory may be used to anchor future studies on assessing the influence of character development techniques on reader engagement in Kenya. Authors and storytellers can benefit from the findings of empirical studies by strategically employing character development techniques to enhance reader engagement in their narratives. While the influence of character development techniques on reader engagement primarily resides within the realm of creative expression, policymakers and educators can play a role in promoting literacy and fostering a culture of reading.